THE INFLUENCED OF THE PROMOTION OF POSITION, WORK ENVIRONMENT AND COMPENSATION OF EMPLOYEES SATISFACTION IN PT. SENTRA DAYA MADANI - Sari, Angraini Puspita (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2025)
This research was conducted at PT. Sentra Daya Madani which engaged in contracting. In the normal course of business, job satisfaction is important for employees as a disgruntled employee will do its job as well as possible for the betterment of the company. For that job satisfaction of employees in a company can be improved by providing promotion, work environment and adequate compensation to employees in accordance with the duties and responsibilities. This type of research is associative. The study population are employees who work in PT. Sentra Daya Madani as many as 58 people, while sampling using a sample census so that the same number of samples with a total population of 58 respondents. The sources of data research using primary data and data collection using survey techniques. Data were analyzed using validity and reliability test, multiple linear regression, test classic assumptions and hypothesis testing. Based on the results, it can be concluded that partial, promotion and working environment positive and significant impact on job satisfaction of employees at PT. Sentra Daya Madani Medan. While compensation and no significant negative effect on job satisfaction of employees at PT. Sentra Power Madani. Simultaneously, the variable promotion, work environment and compensation together positive and significant impact on job satisfaction of employees at PT. Sentra Daya Madani Medan. In the test the coefficient of determination, the value of R = 0.777 means a promotion, work environment and compensation have a strong influence on employee job satisfaction. The coefficient of adjusted R2 = 0.604 meaning the job satisfaction of employees at PT. Sentra Daya Madani Medan able to be explained by the promotion, work environment, and compensation amounting to 60.40% and the remaining 39.60% was explained by other variables outside the scope of the research was not done (for example communication, training, incentives, career development, and so on).